Implementation of Vocational Education in the State of Haryana: Some Insights from the Field Visit - Sridevi, Dr. K V (Voices of Teachers and Teacher Educators, 2020)
This paper attempts to share the experience and insights gained on vocational education during the field visits to schools of Haryana. Vocational education was piloted in the year 2011-12 in 40 schools of Haryana, covering 8 districts with 4000 total number of students enrolled and slowly multiplied in many schools. The planning, implementation, coordination, evaluation of vocational education and associated issues and concerns are highlighted in the paper. The concerns raised by the teachers, students and parents also find place in the paper. On the basis of which, measures to strengthen vocational education in the schools of Haryana have been suggested.